CHARACTERIZATION OF MICROBIAL DIVERSITY AND FATTY ACID COMPOSITION IN THE INTESTINE OF HEALTHY DOMESTIC DUCKS : MICROBIAL COMMUNITY AND FATTY ACIDS PROFILE IN DUCKS INTESTINE - R Susanti; Nur Rahayu Utami; Muchamad Dafip (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Healthy duck gut shows rich bacterial diversity dominated by Firmicutes.- Duck intestine is enriched in saturated fatty acids compared to the feed.- Short chain fatty acids in duck intestine greatly exceed those in the feed.- Genera Lactobacillus and Ruminococcus are key markers of duck gut health.- Palmitic, stearic, and vaccenic acids emerge as major intestinal lipids.ABSTRACTFatty acids exhibit antibacterial properties and serve as metabolic substrates for intestinal bacteria, shaping the composition of the microbiota and the synthesis of microbial metabolites. This study aimed to analyze the duck intestinal microbiota community and its fatty acid profile. This study utilized 25 healthy domestic ducks (Anas platyrhynchos) sourced from an intensive laying farm in Central Java, Indonesia. An exploratory observational research design was employed to analyze data obtained from this study. The intestinal bacteria of duck samples were analyzed using Next-Generation Sequencing (NGS), and fatty acid components using Gas Chromatography–Mass Spectrometry (GC-MS). Duck feed samples were analyzed for nutritional composition using proximate analysis and fatty acid composition using GC-MS. The Simpson and Shannon indices revealed rich microbial diversity in the duck intestine. The abundance of bacteria was dominated by several phyla, such as Firmicutes (82.58%), Actinobacteria (12.25%), and Bacteroidetes (4.27%). The Firmicutes/Bacteroidetes ratio was 19.32, with the intestine containing greater proportion of saturated fatty acids (74.32%) compared to unsaturated fatty acids (33.62%). Additionally, the concentration of short-chain fatty acids (SCFAs) in the duck’s intestine was 15.72 times greater than that found in the feed. Microorganisms, including Bacteroides (2.88%), Faecalibacterium (0.16%), Prevotella (0.08%), Butyricicoccus (0.67%), Ruminococcus (2.2%), Oscillospira (0.02%), and Mucisspirillum (0.018%) are genera that produce SCFA. Bacteria capable of synthesizing medium-chain fatty acids (MCFA) were identified, namely Ruminococcaceae UGC-005 (1.85%) and Acinetobacter (0.005%). Bacteria producing saturated long-chain fatty acids (LCFA) were identified, namely Lactobacillus (12.12%), Prevotella (0.08%), and Alistipes (0.13%). Bacteria capable of producing polyunsaturated fatty acids (PUFA) metabolites including conjugated linoleic acid (CLA) and conjugated linolenic acid (CLnA) were identified, namely Propionibacterium (0.004%), Lactobacillus (12.12%), and Bifidobacterium (0.21%). In summary, the intestinal microbiota of healthy ducks exhibits considerable diversity and a high diversity index. Various bacterial genera contribute to the production of SCFA, MCFA, and LCFA, as well as the conversion of PUFA into CLA and CLnA metabolites. This baseline microbiota–fatty acid profile can guide microbiota-informed feed optimization and candidate probiotic selection to support SCFA production, gut health, and productivity, and it provides a reference for monitoring dysbiosis and evaluating dietary interventions in intensive duck production systems.